Differential associations of sex and age with changes in HRQoL during outpatient cardiac rehabilitation - Lorenza L. S. Lanini; Sebastian Euler; Claudia Zuccarella-Hackl; Rubén Fuentes Artiles; David Niederseer; Bianca Auschra; Roland von Känel; Lena Jellestad (SpringerOpen, 2024)
Abstract Introduction Cardiovascular diseases (CVD) represent the world's leading cause of death. Health-related quality of life (HRQoL) is a widely applied concept of patients' perceived health and is directly linked to CVD morbidity, mortality, and re-hospitalization rates. Cardiac rehabilitation (CR) improves both cardiovascular outcomes and HRQoL. Regrettably, CR is still underutilized, especially in subgroups like women and elderly patients. The aim of our study was to investigate the predictive potential of sex and age on change of HRQoL throughout outpatient CR. Methods 497 patients of outpatient CR were retrospectively assessed from August 2015 to September 2019 at the University Hospital Zurich. A final sample of 153 individuals with full HRQoL data both at CR entry and discharge was analyzed. HRQoL was measured using the 36-Item Short Form Survey (SF-36) with its physical (PCS) and mental (MCS) component scale. In two-factorial analyses of variance, we analyzed sex- and age-specific changes in HRQoL scores throughout CR, adjusting for psychosocial and clinical characteristics. Age was grouped into participants over and under the age of 65. Results In both sexes, mean scores of physical HRQoL improved significantly during CR (p <.001), while mean scores of mental HRQoL improved significantly in men only (p =.003). Women under the age of 65 had significantly greater physical HRQoL improvements throughout CR, compared with men under 65 (p =.043) and women over 65 years of age (p =.014). Sex and age did not predict changes in mental HRQoL throughout CR. Conclusions Younger women in particular benefit from CR with regard to their physical HRQoL. Among older participants, women report equal improvements of physical HRQoL than men. Our results indicate that sex- and age-related aspects of HRQoL outcomes should be considered in CR.